Edukasi Pengenalan dan Pendampingan Manajemen Keuangan pada Remaja Karang Taruna Desa Sentral Baru Kecamatan Bermani Ulu - M. Reza Oktananda; Sucipto Febrianto; Edy Susanto; Charles Charles; Novriza Wahyu Ardiansyah (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
Adolescents are a vulnerable age group susceptible to the influences of a consumptive lifestyle, especially in the digital era of 2025, characterized by the prevalence of online gambling, online gaming, and impulsive financial behaviors. The lack of financial literacy makes many adolescents less capable of managing their finances wisely. This community service activity aims to provide education and guidance in financial management to the youth of Karang Taruna in Sentral Baru Village, Bermani Ulu District. The methods employed include a participatory approach, interactive lectures, budget simulations, personal financial reflections, and direct assistance in saving practices. The results of the activity indicate an increase in participants' understanding of the basic concepts of financial management, awareness of the importance of saving, and the ability to control consumptive behaviors. The concept of financial repentance was introduced as an effective reflective approach to encourage changes in participants' financial behaviors. Financial education has proven to be a preventive and solution-oriented strategy for shaping financially responsible adolescent character. This activity has had a positive impact and can be recommended as a model for financial literacy interventions for adolescents in other rural areas.